Eficiência agronômica e comportamento de formulações de atrazina com taxas distintas de liberação em latossolo vermelho distroférrico - Marchesan, Eli Danieli (2011)
Atrazine (2-chloro-4-ethylamine-6-isopropylamine-striazina) is an herbicide used worldwide to control weeds with potential to contaminate groundwater and harm sensitive crops in succession. The use of controlled release formulations of atrazine could be a strategy to mitigate environmental impact and contribute to improving the efficiency of weed control with atrazine. Aiming to determine the environmental performance and agronomic efficiency of atrazine formulation of controlled release (xerogel), compared with the commercial formulation were conducted one experiment in the field and three bioassays in greenhouse. The field experiment was implemented with the corn, using randomized blocks design, with split plots in a scheme (2 x 6) + 4. In the main plots were located formulations (atrazine xerogel and WG), and in sub-plots the atrazine concentrations (0, 3200, 3600, 4200, 5400 and 8000 g ha-1), with four additional control plots weeded. Soil samples were collected from each plot with 8000 g ha-1 for bioassays in the greenhouse to evaluate the persistence and leaching of the formulations. The experimental designs of bioassays were completely randomized. In the field experiment, we evaluated the density and visual control of weeds and yield of maize. In bioassays, the main variables were height, phytotoxicity, green and dry plant mass. In the first bioassay was selected cultivated species most suitable for use in tests to determine the persistence and leaching of atrazine formulations. In the field experiment, the formulation WG produced greater control of B. plantaginea than xerogel in earlier assessments, but in later assessments atrazine xerogel was more effective. There were no differences in grain yield of maize between the formulations and doses tested. The degree of sensitivity to atrazine varied according to species: okra and peas showed little sensitivity; oats and wheat had an intermediate; radish and tomato had the highest level of sensitivity to the presence of atrazine in soil. The bioavailability of atrazine to soil varied depending on the time and formulation: until 5 days after application, atrazine disponibility by xerogel formulation was higher and in period between 14 and 28 days, the bioavailability of atrazine by WG was higher than by xerogel; 35 days after application, atrazine xerogel showed higher disponibility than the WG. The half-life was 30 and 38 days for atrazine WG and xerogel, respectively. Higher concentrations of atrazine were found in surface soil (0-4 cm) in two formulations. However, the quantification of atrazine by bioassay indicated a greater concentration of WG formulation between 2 and 4 cm, in contrast with the results of chromatographic analysis, which indicated a greater concentration of the xerogel formulation.